2021
DOI: 10.1088/1757-899x/1073/1/012058
|View full text |Cite
|
Sign up to set email alerts
|

Object detection on dental x-ray images using deep learning method

Abstract: Radiological examination has an important role in determining the diagnosis of dental problems and making decisions about the right type of treatment according to the case indications. Dental x-ray is a medical procedure for taking pictures of the inside of the mouth using radiation fluid, where the results are used diagnostically to help the dentist see the entire structure of the jaw bone and teeth, and dental problems that cannot be seen directly. Dental radiographic interpretation, which is generally perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…[ 14 15 ] It has been reported that using an AI algorithm makes it possible to perform radiographic interpretation done by dentists. [ 16 ] Our aim was to develop a deep learning framework to detect and localize trauma and fractures in the mandible.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 15 ] It has been reported that using an AI algorithm makes it possible to perform radiographic interpretation done by dentists. [ 16 ] Our aim was to develop a deep learning framework to detect and localize trauma and fractures in the mandible.…”
Section: Discussionmentioning
confidence: 99%
“…In order to recognize objects from tooth panoramic images from x-rays, Suryani et al . (2021) created a model applying Mask R-CNN, which is a form of the DL approach.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Therefore, to increase the rate of detection, methods of imaging are constantly used (Michou et al ., 2022; Shah et al ., 2014), although dentists can fail to detect early tooth decay lesions even using dental imaging. As a result, the success of diagnosis and therapy rely on both modern technology and the reader's own abilities (Suryani et al ., 2021). In addition, evaluating the images from X-rays also increases the workload for doctors.…”
Section: Introductionmentioning
confidence: 99%
“…Both methods demonstrated high accuracy on caries X-ray image datasets. Some studies, such as that of Suryani et al [ 2 ], have also directly used deep-learning methods for caries detection and identification, which saved time and process steps and improved the simplicity of the method.…”
Section: Related Workmentioning
confidence: 99%
“…With the advances of deep-learning methods in computer vision, many such methods have been applied to caries detection to improve the accuracy of detection and relieve the dentists' workload. For example, Suryani et al [ 2 ] used mask R-CNN to detect objects in dental panoramic X-ray images, which saved time and improved the quality of dentists' diagnoses by automatically detecting panoramic X-ray images. Majanga et al [ 3 ] proposed a deep learning-based technique for dental caries detection named blob detection.…”
Section: Introductionmentioning
confidence: 99%